2017
DOI: 10.1007/s10198-017-0877-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of post-procedural complications on reimbursement, length of stay and mechanical ventilation among patients undergoing transcatheter aortic valve implantation in Germany

Abstract: Background: The impact of various post-procedural complications after transcatheter aortic valve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…25 Other studies have used postinterventional metrics to predict LoS and hospitalisation costs. 30 We have used prospectively only one baseline PROM metric, namely, CFS, to predict hospitalisation costs during TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…25 Other studies have used postinterventional metrics to predict LoS and hospitalisation costs. 30 We have used prospectively only one baseline PROM metric, namely, CFS, to predict hospitalisation costs during TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, parameters such as the prolonged post-procedural mechanical ventilatory and intravenous inotropic support, along with oral inotropic therapy, prior TAVI are risk factors for patient morbidity, probably reflecting a worse general postprocedural clinical status of these patients. Besides, research on TAVI patient series, has consistently found that patients who require mechanical ventilatory support, 16 , 17 and those at New York Heart Association (NYHA) class III/IV 11 have poorer outcome, with higher morbidity and mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Fees are adjusted yearly based on expenditure data from a sample group of German hospitals and are subject to continuous calibration to accurately reimburse cost [15][16][17][18][19][20]. These databases represent a valuable source of national-level health economic data that have been used previously to examine other disorders [21][22][23]. The data are highly detailed and include a wide range of patient characteristics and preexisting conditions.…”
Section: Introductionmentioning
confidence: 99%